The Role of O-GlcNAcylation in Immune Cell Activation - Qiang, Amy; Slawson, Chad; Fields, Patrick E. (Frontiers in Endocrinology, 2021)
O-GlcNAcylation is a dynamic post-translational modification where the sugar, O-linked β-N-acetylglucosamine (O-GlcNAc) is added to or removed from various cytoplasmic, nuclear, and mitochondrial proteins. This modification is regulated by only two enzymes: O-GlcNAc transferase (OGT), which adds O-GlcNAc, and O-GlcNAcase (OGA), which removes the sugar from proteins. O-GlcNAcylation is integral to maintaining normal cellular function, especially in processes such as nutrient sensing, metabolism, transcription, and growth and development of the cell. Aberrant O-GlcNAcylation has been associated with a number of pathological conditions, including, neurodegenerative diseases, cancer, diabetes, and obesity. However, the role of O-GlcNAcylation in immune cell growth/proliferation, or other immune responses, is currently incompletely understood. In this review, we highlight the effects of O-GlcNAcylation on certain cells of the immune system, especially those involved in pro-inflammatory responses associated with diabetes and obesity.